Strengthening antivenom production in Central and South American public laboratories: Report of a workshop - Gutiérrez, José María (2007)
A workshop on antivenom production in Central and South American public laboratories was performed at Instituto Butantan, Sao Paulo, Brazil, from June 12 to June 16, 2006, under the auspices of the program CYTED. The activity was attended by representatives of public laboratories from Costa Rica, Colombia, Perú, Bolivia, Brazil, and Uruguay. Representatives of the World Health Organization (WHO) and the Brazilian Ministry of Health also participated in the workshop. The political, institutional and technological issues related with antivenom manufacture and distribution in these countries were discussed. Current problems on antivenom production and distribution were analyzed, and the need to strengthen collaborative links between countries was stressed, particularly regarding training programs, transfer of technology, and distribution of antivenoms, with the involvement of the Pan American Health Organization and the WHO. Future workshops on other relevant issues, such as quality control and regulatory policies, are being planned, together with collaborative research efforts between the laboratories.